Solid State Fermentation of Citric Acid Production from Raja Banana Peels using Aspergillus niger (Effect of KH2PO4 as Phosphate Sources) - Hidayat, MP., Nur; Khusumawati, Anggraeni Dwi; Perdani, Claudia Gadizza (Journal of Food and Life Sciences, 2019)
Citric acid is the organic acid widely used in food and pharmaceutical industries.The purpose of this study was to determine the effect of adding KH2PO4 as phosphate source of citric acid production from Raja banana peels using Aspergillus niger.The research is used Completely Randomized Design. Concentration of phosphate addition ofÂ  KH2PO4(0%; 0.5%; 1%; 1.5%; and 2%). The fermentation process is done for 7 days. Addition of concentration of KH2PO4 1,5% percentage highest citric acid content that is equal to 38,4% with pH 2,96 and total lowest reducing sugar 36,47 mg/g. This is reinforced by FTIR analysis indicating the presence of citric acid.